Trends in Taxonomy of the Rhodniini Tribe (Hemiptera, Triatominae): Reproductive Incompatibility between Rhodnius neglectus Lent, 1954 and Psammolestes spp. Confirms the Generic Status of Psammolestes Bergroth, 1911 - Ravazi, Amanda [UNESP]; Oliveira, Jader de; Madeira, Fernanda Fernandez [UNESP]; Reis, Yago Visinho dos [UNESP]; Oliveira, Ana Beatriz Bortolozo de [UNESP]; Galvão, Cleber; Azeredo-Oliveira, Maria Tercília Vilela de [UNESP]; Rosa, João Aristeu da [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP] (MDPI, 2022)
The tribe Rhodniini is a monophyletic group composed of 24 species grouped in two genera: Rhodnius and Psammolestes. Rhodnius is a paraphyletic genus formed by 21 species. The event of paraphilia is supported by the greater evolutionary proximity of the species of the prolixus groups with the genus Psammolestes than with the other groups of Rhodnius. Based on this phenomenon, it was proposed the alteration of the genus of the species of Psammolestes to Rhodnius. Thus, we performed experimental crosses between Psammolestes spp. and R. neglectus to assess the degree of reproductive compatibility between Psammolestes and Rhodnius. Hybrids were not obtained for intergeneric crosses. Based on this, we have demonstrated that Rhodnius and Psammolestes have reproductive incompatibility. These data are important to confirm the validity of the specific status of Psammolestes, based on the biological concept of the species.
Keywords: Chagas disease vectors; evolution; experimental crosses; hybridization